Antimalarial activity of the hydroalcoholic crude extract and solvent fractions of Commelina latifolia Hochst. ex C.B.Clarke (Commelinaceae) leaves against Plasmodium berghei in mice. Issue 12 (December 2022) - Tadege, Getnet; Kahssay, Semere Welday; Fisseha, Nebeyi; Abebe, Dehnnet; Nureye, Dejen
Abstract: Ethnopharmacological relevance: In Ethiopia, the indigenous medicinal plant Commelina latifolia Hochst. ex C.B. Clarke leaves are used to treat malaria and wounds. Aim of the study: In this work, the antiplasmodial activity of Commelina latifolia crude leaf extract and solvent fractions against Plasmodium berghei -infected mice was investigated. Materials and methods: 80% methanol was used to extract the leaves of C. latifolia, and the crude extract was fractionated using chloroform, pure methanol, and distilled water. All test compounds were undergone an acute oral toxicity test before being put through Peter's 4-day suppressive test to see if they have antiplasmodial activity. The hydroalcoholic crude extract and chloroform fraction were additionally assessed for antimalarial activity using curative and prophylactic tests in P. berghei- infected laboratory mice. Results: All of the tested crude extracts were safe at a dose of 2000 mg/kg. At 400 mg/kg dose both the 80% methanol extract and chloroform fraction exhibited antimalarial activity with parasitemia suppression values of 86.31%, and 76.56% in the four-day suppressive test, 81.97% and 72.05% in Rane's test, and 69.05% and 62.88% in the prophylactic test, respectively. Conclusion: Collectively, the oral dose of Commelina latifolia is safe, and reveals promising antimalarial activity. The findings backed up the utilization of the plant in traditional medicine to treat malaria. Abstract : Antimalarial activity; Commelina latifolia ; Plasmodium berghei ; Traditional medicine.